Numerical Investigation of Thermophysical Processes Accompanying the Solid-Phase Synthesis of a Multilayer Composite Taking into Account the Melting Reactive Layer; AIP Conference Proceedings; Vol. 1683 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures - Aligozhina K. A. Kamila Abaevna (2015, 2015)
Title screen